FACTORS THAT AFFECTING WOMEN'S STRUGGLE IN ACHING ECHELON POSITIONS IN THE LOCAL GOVERNMENT OFFICES OF NORTH SULAWESI PROVINCE - Dwianita Conny Palar; I Ketut Ardhana; Ni Made Wiasti; I Nyoman sukiada (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2023)
Every civil servant has the same opportunity to get a position to improve their career, including employees in the North Sulawesi Provincial Government Office. The structural position is a very strategic position for anyone who can reach the position. However, it is not uncommon to find gender inequality in a community group that can affect every employee in reaching the position. As for this study, it can be understood that there are several factors that cause an imbalance in occupying echelon positions. The existing factors are divided into internal factors that come from within the employee, and external factors that come from outside the employee and influence them to develop themselves, especially for female employees. All of these factors are expected to create gender equality in the Regional Government of North Sulawesi. Keywords: Women's struggle, Minahasa culture, local government